KERAGAMAN FLORISTIK DAN STATUS KETERANCAMAN KEPUNAHAN JENIS TUMBUHAN DI KAWASAN AIR TERJUN BUNBUN KABUPATEN MURUNG RAYA (Floristic Diversity and Extinction Threat Status of Plants at the Bunbun Waterfall Region, Murung Raya Regency) : Setiarno - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACT This research is concerning the floristic diversity and status of extinction threat of class of plants at the Bunbun Waterfall region, Uut Murung sub Regency, Murung Raya Regency, Central Kalimantan Province. The purpose of this research was intended to find out the composition, diversity, and threat status of plants based on Government Regulation (PP) Nomor 7/1999 about Indonesia Scarce Plants and IUCN Global Red List. The research was using combination between the way of path and the way of blocked path. The research result showed that there are 42 kinds of trees, whereas six of which are assigned into critically endangered category of IUCN, like as gaharu (Aquilaria beccariana), keruing (Dipterocarpus cornutus), meranti kuning (Shorea macroptera), meranti merah (Shorea leprosula), meranti putih (Shorea lamellata) and ulin (Eusideroxylon zwageri). Shorea macroptera is assigned into endangered category, meanwhile Eusideroxylon zwageri and Aquilaria beccariana are assigned into vulnerable category based on IUCN. Shorea leprosula is a class which has the greatest essential value in whole growth stage, whereas Eugenia europholia, Shorea uliginosa and Shorea leprosula are dominant classes at each stage of growth. The index of tree diversity is classified into moderate category. Keywords: Floristic diversity, extinction threat status of plants, IUCN.